Trends in Quality-Adjusted Skill Premia in the United States, 1960–2000 - Carneiro, Pedro; Lee, Sokbae (American Economic Review, 2011)
This paper presents new evidence that increases in college enrollment lead to a decline in the average quality of college graduates between 1960 and 2000, resulting in a decrease of 6 percentage points in the college premium. A standard demand and supply framework can qualitatively account for the trend in the college and age premia over this period, but substantial quantitative adjustments are needed to account for changes in quality. (JEL I23, J24, J31)